2005
DOI: 10.1007/s10789-005-0094-0
|View full text |Cite
|
Sign up to set email alerts
|

Properties of macroporous aluminosilicate ceramics modified with oligomeric aluminum phosphates

Abstract: The chemical interaction between oligomeric aluminum phosphate solutions and the surface of macroporous aluminosilicate ceramics is studied. It is shown that the resulting composite material has markedly enhanced mechanical strength, with no significant reduction in porosity (80-85% of the initial value).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kinetics of mercury adsorption from waste water using activated carbon has been reported by Mohan et al [11]. In our laboratories [12,13] and literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27] the evaluation of the ion exchange properties of various synthetic inorganic ion exchange materials indicated that, most of inorganic ion exchanger loss its capacities or great extent of its capacities when treated at high temperature. So in this work we attempt to overcome of these problems by thermal treatment of the exchangers in the loaded form at high temperature to construct the material by keeping ionic bonding for exchangeable ions in framework of coordination bonding.…”
Section: Introductionmentioning
confidence: 82%
“…Kinetics of mercury adsorption from waste water using activated carbon has been reported by Mohan et al [11]. In our laboratories [12,13] and literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27] the evaluation of the ion exchange properties of various synthetic inorganic ion exchange materials indicated that, most of inorganic ion exchanger loss its capacities or great extent of its capacities when treated at high temperature. So in this work we attempt to overcome of these problems by thermal treatment of the exchangers in the loaded form at high temperature to construct the material by keeping ionic bonding for exchangeable ions in framework of coordination bonding.…”
Section: Introductionmentioning
confidence: 82%